Clustering of Depression and Inflammation in Adolescents Previously Exposed to Childhood Adversity - Miller, Gregory E.; Cole, Steve W. (Biological psychiatry (1969), 2012)
There is mounting interest in the hypothesis that inflammation contributes to the pathogenesis of depression and underlies depressed patients' vulnerability to comorbid medical conditions. However, research on depression and inflammation has yielded conflicting findings, fostering speculation that these conditions associate only in certain subgroups, such as patients exposed to childhood adversity. We studied 147 female adolescents. All were in good health at baseline but at high risk for depression because of family history or cognitive vulnerability. Subjects were assessed every 6 months for 2.5 years, undergoing diagnostic interviews and venipuncture for measurement of two inflammatory biomarkers, C-reactive protein (CRP) and interleukin-6 (IL-6). Childhood adversity was indexed by parental separation, low socioeconomic status, and familial psychopathology. Multilevel models indicated that childhood adversity promotes clustering of depression and inflammation. Among subjects exposed to high childhood adversity, the transition to depression was accompanied by increases in both CRP and IL-6. Higher CRP remained evident 6 months later, even after depressive symptoms had abated. These lingering effects were bidirectional, such that among subjects with childhood adversity, high IL-6 forecasted depression 6 months later, even after concurrent inflammation was considered. This coupling of depression and inflammation was not apparent in subjects without childhood adversity. These findings suggest that childhood adversity promotes the formation of a neuroimmune pipeline in which inflammatory signaling between the brain and periphery is amplified. Once established, this pipeline leads to a coupling of depression and inflammation, which may contribute to later affective difficulties and biomedical complications.